2018
DOI: 10.21276/apalm.1750
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Manifestation in Lung, Breast and Git Malignencies :A Discriptive Study

Abstract: Background: Malignancy is one of the principle causes of death both in developed and developing countries.Methods: 102 lung, GIT and Breast malignancies patients were selected. The various hematological abnormalities in lung, GIT and breast malignancies were evaluated by estimation of hematological parameter. Complete hematological investigation was performed using Abbott cell-3700dyn hematology analyzer and peripheral smear using Field's stain.Result: Hematological abnormalities were seen in Lung, GIT and Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
(9 reference statements)
3
2
1
Order By: Relevance
“…21patients were microcytic hypochromic. We found normocytic hypochromic to be the most common, which is different from other studies who found normocytic normochromic the most common type of anemia [1,2].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…21patients were microcytic hypochromic. We found normocytic hypochromic to be the most common, which is different from other studies who found normocytic normochromic the most common type of anemia [1,2].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study on 98 newly diagnosed solid tumor patients, we found anemia was present in 89 (90.82%) patients. This frequency was close to the reports by other studies by [1,2,6,7].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations